Power Doppler and grey scale ultrasonography of lower limb entheses in ankylosing spondylitis - Kiris, A.; Kaya, A.; Ozgocmen, S.; Kocakoc, E. (B M J Publishing Group, 2007)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR 2007) -- JUN 13-16, 2007 -- Barcelona, SPAIN